Strategi Praktis Untuk Mempercepat Ekonomi Sirkular Pada Rantai Pasokan Bawang Merah Lokal Varietas Rubaru - Nazizah, Fitrotin; Sustiyana, Sustiyana (Universitas Islam Madura, 2025)
The implementation of the circular economy concept in the local shallot supply chain of the Rubaru variety still faces various obstacles that need to be overcome. The aim of this research is to determine the level of understanding of the parties involved in the Rubaru variety shallot supply chain regarding the circular economy concept, evaluate its implementation, and formulate strategies that can accelerate the circular economy in the Rubaru variety local shallot supply chain. This research is dominated by qualitative descriptive analysis research supported by SWOT analysis. The research results show that the level of understanding and application of the circular economy concept of parties involved in the Rubaru variety of shallot supply chain is still low because the term circular economy is relatively new. But farmers, agro-industry and household consumers are already implementing simple recycling and reuse concepts. The strategy to accelerate the implementation of a circular economy in the Rubaru variety of red onion supply chain requires increasing synergy between the parties involved, especially in terms of collaboration between farmers, traders, agro-industry and consumers. The development of derivative products such as fried onions, organic fertilizer, bioenergy and shallot paste opens up great opportunities to increase the economic value of shallots while reducing waste.